The Effect of Combined Treatment of Alpha-Tocopherol, Ascorbic Acid, and Pyridoxine with NMDA Blocker Memantine on Penicillin-Induced Epileptiform Activity in Rats - Aydın, D.; Yildirim, M.; Ayyildiz, M.; Aǧar, E. (TÜBİTAK Scientific & Technical Research Council Turkey, 2013)
Aim: To evaluate the effects of coadministration of vitamins alpha-tocopherol, ascorbic acid, and pyridoxine with memantine on a penicillin-induced experimental epilepsy model in rats so as to clarify the eventual interaction between these vitamins and the N-methyl- D-aspartate (NMDA) system. Materials and methods: The epileptic focus was produced by intracortical penicillin G potassium injection. The effects of intraperitoneal injections of memantine, memantine + alpha-tocopherol, memantine + ascorbic acid, and memantine + pyridoxine combinations on epileptiform activity were evaluated in electrocorticogram recordings. Results: The antiepileptiform effects appeared earlier in all memantine and vitamin coadministrated groups compared to the memantine-alone group, but the difference between the groups was not statistically significant considering the frequency and amplitude of the epileptiform activity. Conclusion: Coadministration of vitamins does not enhance the antiepileptiform activity of memantine in penicillin-induced epilepsy in rats. However, this coadministration causes the earlier appearance of antiseizure effects. Since moderate doses of these vitamins have no side effects, it might be a good idea to use them with NMDA blockers to provide an earlier antiepileptic effect. © TÜBİTAK.
Keywords: Alpha-Tocopherol; Ascorbic Acid; Experimental Epilepsy; Memantine; NMDA; Pyridoxine